1985
DOI: 10.2170/jjphysiol.35.841
|View full text |Cite
|
Sign up to set email alerts
|

Tension development in frog skeletal muscle induced by silver ions.

Abstract: In single fibers of frog toe muscles placed in a Cl-free MOPS solution containing 1.8 mM Ca2+, tension developed slowly in the presence of very low concentrations of Ag+. This tension was not blocked by the administration of Co2+ or Nit +. On the other hand, two types of transient tensions developed with the application of 5 µM Ag+, in fibers pretreated with 0-Ca2+ MOPS solution, containing either 2 mM Co2+ or 1 mM Ni2+, for 10 min. In the presence of divalent cations or TTX, the first repetitive twitch-like c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

1987
1987
1992
1992

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…Treatment of a frog skeletal muscle fiber with 10 ,uM Ag+ induced a transient contraction (Fig. 1 A) as previously reported by Oba and Hotta (7,8). Even after a subsequent wash with Ca> free nitrate Ringer and with Ringer (to remove Ag+), there was a complete inhibition of twitch, tetanus, and K+-induced tension.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Treatment of a frog skeletal muscle fiber with 10 ,uM Ag+ induced a transient contraction (Fig. 1 A) as previously reported by Oba and Hotta (7,8). Even after a subsequent wash with Ca> free nitrate Ringer and with Ringer (to remove Ag+), there was a complete inhibition of twitch, tetanus, and K+-induced tension.…”
Section: Resultssupporting
confidence: 84%
“…These Ag+ contractions occur without membrane depolarization and in the presence of tetrodotoxin (8). They are abolished when the fiber is detubulated (by glycerine Ringer), suggesting a direct effect of Ag+ on E-C coupling at the level ofthe T-tubular system (7,8). Since the T-tubular Ca> channels are essential to E-C coupling, we examined the possibility that Ag+ interacts with the Ca" channel to produce contraction and the subsequent failure of E-C coupling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This mechanism is well established as the Ca2+-induced Ca2 + release one, since the original works of ENDO et al (1970) and FORD and PODOLSKY (1970). On the other hand, we found that similar amounts of Ag+ used above induced tonic contracture in single skeletal muscle fibers immersed in a solution containing more than 0.2 mM of Ca2 + (OBA and HOTTA, 1985a). These findings suggest that these Ag+-induced contractures may be atrributed to external Ca2 + or T-tubular membrane bound Ca2 + .…”
supporting
confidence: 68%
“…In either case, the maximum concentration of diltiazem used here (100 jiM) would abolish most Cat + currents which flow across the T-tubular membranes. Furthermore, our previous study showed that 5jM Ag+ caused the contracture in fibres treated for more than 30 min with Ca2+-free solution containing 3 mM EGTA in which T-tubular membrane bound Ca2 + would largely be removed (OBA and HOTTA, 1985a). These findings, therefore, suggest that the Ca2 + -induced Ca2 + release mechanism does not seem to be involved in the initiation of Ag+-induced phasic contracture.…”
Section: Discussionmentioning
confidence: 83%